Remembrance of Marshal Stepa Stepanović in Čačak between (trans-)national memory and local politics. (22nd November 2019) - Baković, Nikola
ABSTRACT: The article analyses commemorative practices and public debates revolving around the local remembrance of military commander Marshal Stepa Stepanović in the Serbian town of Čačak. The geographical concept of place is used as the coming together of processes and agencies operating on different scales (local, national, transnational) and manifesting themselves through material settings around which social interactions take place. It is argued that Stepanović's legacy served as a medium for directing how different groups within the local community processed contentious historical experiences, concurrently revealing polyphonous collective and individual interests and agencies. Ultimately, this example of local remembrance can be viewed as a microcosm of wider mnemonic dynamics in Serbian society, as well as of the influences of broader processes on locally based social relations.